Detection and classification of wipe transitions in sport videos in presence of object motion - Chavan, Salim; Narayana, M; Koteswara Rao,, L (International Journal of Engineering and Technology, 2018)
Transition detection is the necessary step in retrieval and investigation of videos on the basis of contents. Since last two decades, most of the researchers are involved in developing algorithms for detection of gradual transitions. However, the features of all gradual transitions are different and hence this issue still needs to be addressed precisely. After identifying this issue, an integrated shot boundary detection method is proposed in this paper. Wipe transition is the effect which is mostly used in the video making industries .Since there are different types of wipe transitions, it becomes very difficult to detect such transitions. Due to complexity in detection of wipes due to noise, object and camera motion earlier methods have less focus on this issue. In this paper an efficient wipe detection method is presented which gives better results even in the presence of object and camera movements.